English - vietnamese and Vietnamese - English dictionary of environment (Hà Nội, 1995)
Sách giới thiệu và giải thích khá rõ ràng, chính xác gần 3.000 thuật ngữ về ngành khoa học môi trường
Keywords: Environment sciences; Terminology